Trade unions' changing role : membership erosion, organisational reform, and social partnership in Europe - Ebbinghaus, Bernhard (Cologne: Max Planck Institute for the Study of Societies, 2002)
"Bernhard Ebbinghaus DIGITAAL TE RAADPLEGEN IN DE LEESZAALEen verkorte versie zal verschijnen in het Europese Jaaroverzicht 2001/2002, uitg. door Mike Terry (Speciaal nummer, Industrial Relations Journal, december 2002)"